2021
DOI: 10.1039/d1ra02219a
|View full text |Cite
|
Sign up to set email alerts
|

A pH-sensitive, stimuli-responsive, superabsorbent, smart hydrogel from psyllium (Plantago ovata) for intelligent drug delivery

Abstract: Herein, we report the dynamic swelling, stimuli responsive swelling-deswelling properties, sub-acute toxicity studies and sustained drug release potential of a polysaccharide-based hydrogel isolated from psyllium husk (a well-known dietary fiber).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…The absorption band at 1612 cm −1 in unmodified ALH disappears in CL-ALH as the ester carbonyl signals, due to the successful crosslinking of ALH with CA, appeared at 1728 cm −1 . 32 The signals of the polymeric backbone of CL-ALH appeared at 2901 cm −1 is due to –CH 2 symmetric and –CH stretching vibration whereas the hydroxyl signals in CL-ALH appeared at 3551 cm −1 . The stretching vibrations of ether linkage (C–O–C) in ALH spectrum 32 were shifted from 1047 cm −1 towards a higher wavenumber, 1081 cm −1 after cross-linking as shown in the FTIR spectrum of CL-ALH (Fig.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The absorption band at 1612 cm −1 in unmodified ALH disappears in CL-ALH as the ester carbonyl signals, due to the successful crosslinking of ALH with CA, appeared at 1728 cm −1 . 32 The signals of the polymeric backbone of CL-ALH appeared at 2901 cm −1 is due to –CH 2 symmetric and –CH stretching vibration whereas the hydroxyl signals in CL-ALH appeared at 3551 cm −1 . The stretching vibrations of ether linkage (C–O–C) in ALH spectrum 32 were shifted from 1047 cm −1 towards a higher wavenumber, 1081 cm −1 after cross-linking as shown in the FTIR spectrum of CL-ALH (Fig.…”
Section: Resultsmentioning
confidence: 96%
“…Whereas, the literature has indicated the presence of signals at 105.56 ppm for C1 and 63.24 to 79.33 ppm for C2-6 for unmodified ALH. 32 The upfield shifting in all signals of ALH after crosslinking with CA, especially the carbonyl region indicated the formation of ester bonds between ALH and CA.…”
Section: Resultsmentioning
confidence: 97%
“…Interestingly, Hussain et al isolated polysaccharide-based stimuli-responsive hydrogel from arabinoxylan, basil seed, linseed, , Salvia spinosa seeds, and glucuronoxylan ,, for distinctive drug delivery. Primarily, these hydrogels do not utilize any chemical cross-linking agents for fabrication.…”
Section: Hydrogel Cross-linking Methodsmentioning
confidence: 99%
“…130 Additionally, Li et al reported phenylboronic modified chitosan and oxidized dextran hydrogel that were able to undergo covalent cross-linking through imine bond and phenylboronate ester for pH and glucose-responsive drug delivery. 131 Interestingly, Hussain et al isolated polysaccharide-based stimuli-responsive hydrogel from arabinoxylan, 20 basil seed, 21 linseed, 132,133 Salvia spinosa seeds, 134 and glucuronoxylan 33,135,136 for distinctive drug delivery. Primarily, these hydrogels do not utilize any chemical cross-linking agents for fabrication.…”
Section: Click Chemistrymentioning
confidence: 99%